Cognitive and emotional disturbances in adult patients with myotonic dystrophy type 1 - E. K. Erokhina; K. V. Shamtieva; E. A. Melnik; D. O. Kazakov; S. A. Kurbatov; E. P. Pavlikova; O. A. Tikhonova; E. A. Mershina; V. E. Sinitsyn; D. V. Vlodavets (Нервно-мышечные болезни, 2024)
Background. Myotonic dystrophy type 1 (DM1) is a hereditary slowly progressive multisystem disease with an autosomal dominant mode of inheritance, caused by the expansion of trinucleotide (CTG)n repeats in the 3’ untranslated region of the DMPK gene. Among the clinical manifestations of DM1, an important place is occupied by symptoms of damage to the central nervous system, in particular cognitive and emotional disorders.Aim. To evaluate the type of cognitive and emotional impairments in patients with different forms of DM1 and their impact on quality of life.Materials and methods. 60 patients with genetically confirmed DM1 were examined (average age 37.0 ± 12.4 years; 36 (60.0 %) of them were men). All patients underwent neuropsychological testing using the Montreal Cognitive RatingScale, Mini‑Mental State Examination, Addenbrooke’s III, Wechsler tests, pathfinding, symbolic and numeric modalities, Luria’s 10 Words, Frontal Dysfunction Battery; assessment of emotional disturbances using the Hospital Anxiety and Depression Rating Scale and the Apathy Scale; quality of life assessment –  36‑Item Short‑Form Medical Outcomes Study. Brain magnetic resonance imaging was performed in 53 patients to assess the severity of white matter lesions and gray matter atrophy.Results. The study included 8 (13.3 %) patients with congenital, 19 (31.7 %) – childhood, 33 (55 %) – adult forms of MD1. The group of patients with the congenital form had the most severe cognitive deficits, especially in tests of executive functions and visuospatial perception. Cognitive impairment was also characteristic of the adult form, but to a lesser extent. Compared to controls, patients with DM1 were significantly more likely to exhibit apathy (p = 0.002) rather than anxiety and depression. In DM1, damage to both the white and gray matter of the brain was established, and a connection between damage to the gray matter and depression (r = 0.296) and apathy (r = –0.291) was revealed. The quality of life is largely influenced by emotional disorders (anxiety, r = –0.577; depression, r = –0.650; apathy, r = –0.545).Conclusion. In patients with DM1, a typical pattern of cognitive impairment has not been identified; different domains of cognitive functions are affected. The greatest cognitive deficit is typical for the group of patients with the congenital form. A connection between damage to the gray matter of the brain and emotional disorders has been revealed.The presence of the latter reduces the quality of life of patients with DM1.